All United Malay Mechanic Motorsport / Iskandar Zulkarnain Ridzuan ... [et al.] - Ridzuan, Iskandar Zulkarnain; Saufi, Mohd Hafizi; Kamaruzzaman, Mohd Haszaruddin; Che Embi, Arjuna Setiabudhi; Abdullah Sani, Muhd Firdaus; Isa, Nor Anas (Faculty of Information Management, 2003)
From the research and survey that have been done, from our opinion our business plan have a big potential and opportunity to success. Mostly it is because of the need and wants from the customers plus a high demand on this business make us believe that we have a better opportunity to success. Beside that, these types of business still not available in this location where we have choose. Therefore, we believe that we may monopoly and control the market in this area.